2013
DOI: 10.1021/ja402053d
|View full text |Cite
|
Sign up to set email alerts
|

Azaphosphatranes as Structurally Tunable Organocatalysts for Carbonate Synthesis from CO2 and Epoxides

Abstract: Three azaphosphatranes were used as organocatalysts for the synthesis of cyclic carbonates from CO2 and epoxides. They proved to be efficient single-component, metal-free catalysts for the reaction of simple or activated epoxides (styrene oxide, epichlorohydrin, glycidyl methyl ether) with CO2 under mild reaction conditions, displaying high stability and productivity over several days of reaction. Substitution patterns on the catalyst were shown to affect activity and stability. Kinetic analysis allowed invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(113 citation statements)
references
References 43 publications
3
108
0
2
Order By: Relevance
“…Interestingly, the synthesis of the cyclic carbonate products could be done under highly mild conditions (T = 25−45 o C, p(CO 2 ) = 10 bar), providing a low net CO 2 emission reaction setup. When compared to a previously reported metal based catalytic system, comprising of a Lewis acidic Zn(salphen) catalyst and using Bu 4 Dufaud et al 116 recently developed a green method using azaphosphatranes as catalysts. This method allows for the efficient coupling of epoxides and CO 2 at 80 o C and atmospheric pressure of CO 2 using a 0.1 mol % of catalyst loading.…”
Section: Scheme 8 Preparation Of Heterocyclic Structures From the Reamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the synthesis of the cyclic carbonate products could be done under highly mild conditions (T = 25−45 o C, p(CO 2 ) = 10 bar), providing a low net CO 2 emission reaction setup. When compared to a previously reported metal based catalytic system, comprising of a Lewis acidic Zn(salphen) catalyst and using Bu 4 Dufaud et al 116 recently developed a green method using azaphosphatranes as catalysts. This method allows for the efficient coupling of epoxides and CO 2 at 80 o C and atmospheric pressure of CO 2 using a 0.1 mol % of catalyst loading.…”
Section: Scheme 8 Preparation Of Heterocyclic Structures From the Reamentioning
confidence: 99%
“…This study on supramolecular catalysis also provided new evidence concerning the previously proposed mechanism involving the simultaneous dual activation of the epoxide and CO 2 . 116 The hemicryptophane was carefully chosen as a building block to construct the cages. This aspect deserves to be highlighted as it allowed the use of only 0.1 mol % of catalyst, although most of the known supramolecular catalysts suffer from product inhibition and have to be used in stoichiometric amounts.…”
Section: Scheme 8 Preparation Of Heterocyclic Structures From the Reamentioning
confidence: 99%
“…This is in sharp contrast with our previous results related to the use of azaphosphatranes as phase-transfer catalysts or organocatalysts for CO 2 conversion. [6][7][8][9][10] In both these previous cases, [1a·H]…”
Section: Catalytic Properties In the Rop Of Lactidementioning
confidence: 99%
“…[5] Martinez et al have also reported the use of these azaphosphatranes as highly active and robust phase-transfer catalysts, and as organocatalysts for the synthesis of cyclic carbonates from CO 2 and epoxides. [6][7][8][9][10] In the latter reaction, the mechanism was shown to involve an initial activation step of the epoxide through formation of a hydrogen bond with the P + -H group of the azaphosphatrane. This recent result encouraged us to further explore the use of this original cation as an organocatalyst in the activation of C=O groups.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these new greener processes involve the use of ionic liquids [17], organocatalysts [18][19][20][21][22][23], supercritical CO 2 [24,25], or metal-based photocatalysts [26,27] although the most commonly used catalysis methodology for the synthesis of these compounds is the metal-catalyzed "cycloaddition" of carbon dioxide to small heterocyclic substrates better referred to as CO 2 /substrate couplings. The use of ring-strained substrates thermodynamically favors the formation of the heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%